1960
DOI: 10.1126/science.131.3406.1040
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Differentiation of Epididymal and Seminal Spermatozoa of the Rabbit

Abstract: Rabbit spermatozoa from the epididymis lack the antigenic material present on seminal spermatozoa, which these latter cells have in common with the seminal plasma. This observation provides further support for the indirect evidence, obtained previously, that antigenic material is taken up by the spermatozoa from the seminal plasma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

1964
1964
1985
1985

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 7 publications
3
16
0
Order By: Relevance
“…Basically identical findings were obtained on the antigenic spectrum of all seminal products when antisera to rabbit seminal plasma were substituted for antisera to washed ejaculated rabbit spermatozoa. This agreed with the concept that sperm-coating antigens were of seminal plasma origin (Weil, 1960 (Weil, 1960). The term, sperm-coating antigens, has been used to describe that phenomenon.…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…Basically identical findings were obtained on the antigenic spectrum of all seminal products when antisera to rabbit seminal plasma were substituted for antisera to washed ejaculated rabbit spermatozoa. This agreed with the concept that sperm-coating antigens were of seminal plasma origin (Weil, 1960 (Weil, 1960). The term, sperm-coating antigens, has been used to describe that phenomenon.…”
Section: Resultssupporting
confidence: 62%
“…In another area, Weil (1960) reported that rabbit spermatozoa were coated with seminal plasma antigens during ejaculation. Hunter & Hafs (1965) confirmed this and reported that antigenic coating also occurred upon passing through the epididymis.…”
Section: Introductionmentioning
confidence: 99%
“…Matsunaga & Hiraizumi, 1962;Behrman, Buettner-Janusch, Heglar, Gershowitz & Tew, 1960 (Weil & Rodenburg, 1960 (Weil, 1960). Antigens are evidently present on rabbit spermatozoa since those from the epididymis were agglutinated by auto-antibodies against semen (Edwards, 1960).…”
Section: Mixed Agglutination Reactionmentioning
confidence: 99%
“…However, McLaren (1964) reported a marked depression of fertility after active immunization with mouse spermatozoa and a close association between the sperm-agglutina¬ tion titre of the serum and a reduction of litter size. Edwards (1964) (Snell & Poucher, 1943), the source of the antigen (Edwards, 1960a;Henle, Henle & Chambers, 1938;Menge & Protzman, 1967;Weil, 1960;Weil & Roberts, 1965;Willson & Katsh, 1965) (Edwards, 1960b;Parson & Hyde, 1940) and there were claims that vaginal absorption of homologous spermatozoa would induce an antibody response as well as cause a reduction of fertility McCartney, 1923;Otani, Behrman, Porter & Nakayama, 1963;Pommerenke, 1928). Local antibody production by the vagina might also have a significant role after intravaginal immunization, since Bell & Wolf (1967) (Dixon & Mood, 1946). difference between slopes in either period ( The antigen chosen to induce infertility has been found to be of prime impor¬ tance.…”
Section: Introductionmentioning
confidence: 99%